Regulation of Global Transcription in Escherichia coli by Rsd and 6S RNA. Issue 6 (1st June 2018) - Lal, Avantika; Krishna, Sandeep; Seshasayee, Aswin Sai Narain
Abstract: In Escherichia coli, the sigma factor σ 70 directs RNA polymerase to transcribe growth-related genes, while σ 38 directs transcription of stress response genes during stationary phase. Two molecules hypothesized to regulate RNA polymerase are the protein Rsd, which binds to σ 70, and the non-coding 6S RNA which binds to the RNA polymerase-σ 70 holoenzyme. Despite multiple studies, the functions of Rsd and 6S RNA remain controversial. Here we use RNA-Seq in five phases of growth to elucidate their function on a genome-wide scale. We show that Rsd and 6S RNA facilitate σ 38 activity throughout bacterial growth, while 6S RNA also regulates widely different genes depending upon growth phase. We discover novel interactions between 6S RNA and Rsd and show widespread expression changes in a strain lacking both regulators. Finally, we present a mathematical model of transcription which highlights the crosstalk between Rsd and 6S RNA as a crucial factor in controlling sigma factor competition and global gene expression.